Globalization and internationalization of Higher Education : towards critical relationalities and postcolonial solidarity based on the accounts of non-Western European students at the University of Iceland - Armando Garcia Teixeira 1984- (2024)
This thesis builds on the overarching theoretical framework of Critical Internationalization Studies (CIS) in the field of Internationalization of Higher Education (IHE), more precisely, what is known as internationalization otherwise, and deploys a postcolonial lens to contextualize the accounts of non-Western European students from post-socialist countries enrolled at UI. This postcolonial theoretical framework is based on two instances. First, Said’s Orientalism and Herder’s Romantic Nationalism, is used to conceptualize this population of International Students as exotic insiders within the Icelandic setting. While the concepts of racial triangulation, global white supremacy and precarity are used in the interpretation of the students’ accounts. The methodology relies on the content analysis of in-depth and semi-structured interviews (approx. 5,5 hours of recording and 126 pages of transcripts) concerning ISEP students’ subjective experiences in UI and broader societal contexts. To this, the author’s reflexive narrative account as a constitutive member of this student population is added to substantiate the research findings and explore practical avenues. The researcher conducted one group interview with three participants and three individual interviews. Students were given the option to either choose to participate in a group or individually. Some opted for individual to preserve their identity. The arguments put forward in this research are based on the analysis of the transcripts. By approaching IHE through a rather unexplored angle within Icelandic research, this research aims to pave the way for postcolonial alliances and solidarities, bring attention to core issues of precarity, neoliberal globalization and IHE processes and practices in late modernity. Þessi ritgerð byggir á yfirgripsmiklum fræðilegum ramma gagnrýninna alþjóðavæðingarfræða (e. Critical Internationalization Studies, CIS) á sviði alþjóðavæðingar háskólamenntunar (e. Internationalization of Higher Education, IHE), nánar tiltekið ...